FEATURES OF CREATION AND ACTIVITIES OF LEGAL ENTITIES UNDER THE CURRENT LEGISLATION OF UKRAINE - Слободська, Ірина Андріївна; Буцька, Тетяна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Objective: to analyze the national legislation regarding the specifics of creating a legal entity, to consider the problematic issues of registration and formation of a legal entity at the current stage in the context of adapting legislation for legal entities with international standards. Research methods: the use of the dialectical method of knowledge allowed us to concentrate the accumulated scientific knowledge and practice of applying legislation on the legal basis for creating a legal entity. Results: investigated the issue of registration of legal entities, the main problems of their operation. The conclusion was made: that the emergence of a legal entity must comply with the rules established by current legislation, and new legislative changes are in line with the trends to improve legislation in relation to legal entities. Discussion: legislation with respect to legal entities, changes, namely the adoption of a new Law of Ukraine «On Limited and Additional Liability Companies», which aims to harmonize the legislation governing the activities of LLC and ALC to European standards. The emergence of a legal entity is impossible without certain constituent documents, which may be: a regulatory act or a statute (a provision), or a founding agreement and statute, or minutes of meetings, etc. The constituent documents must indicate the name of the legal entity, its location, purpose and subject of activity, the composition and competence of its bodies, as well as other information provided by the legislation on legal entities of the appropriate type. Constituent documents may contain other details that are not in conflict with the law. Methods of legal influence on the formation and activities of legal entities coincide in many countries, and typical types of their organizational and legal forms, however, each country has specific features, due to historical, political and other circumstances. Regarding the statistics for the past year, and this year - the data on registration of the creation of legal entities significantly decreased. But this may change if the country’s economy changes and appropriate economic reforms take place.